ksplorasi Metode Bayani Aisyah Bint Syathi’ Dalam Al-Tafsir Al-Bayani Li Al-Qur’an Al-Karim - Wanda Jawhariyah Sya'baniyah; Astri Vitria Febiani; Nilna Faiziya (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
The development of modern Qur'anic exegesis signalled a methodological shift from classical approaches to more linguistic and literary ones, which emphasise the beauty and expressive power of Qur'anic language. A key figure in this transformation was Aisyah ‘Abd al-Rahman Bint al-Syathi’, whose work al-Tafsir al-Bayani li al-Qur’an al-Karim exemplifies this shift. This study aims to describe the fundamental principles, patterns and bayani methods employed by Bint al-Syathi within the context of contemporary Qur'anic interpretation. This study employs a qualitative descriptive method with a library research approach, utilising primary sources such as Al-Tafsir Al-Bayani Li Al-Qur'an Al-Karim, as well as secondary sources from related academic studies. The findings demonstrate that the bayani method prioritises linguistic, rhetorical, and stylistic analysis to reveal divine meanings, eschewing reliance on Israiliyyat narratives or excessive scientific interpretations. In conclusion, the bayani method makes a significant contribution to the renewal of modern Qur'anic exegesis by positioning language as the primary means of understanding the Qur'an's spiritual, moral, and aesthetic messages in a rational and contextual manner.